Data Processing Method in Medium Range Coastal Radar Complex - Dang Quang Hieu; Nguyen Xuan Truong (Известия высших учебных заведений России: Радиоэлектроника)
The article presents the basic principles of design and development of integrated middle range Coastal Surveillance System (CSS) used for water surface lookout. It provides solutions for such missions as command and control of maritime forces, border monitoring and control, prevention of illegal activities such as piracy, smuggling, illegal immigration, illegal fishing, supporting search and rescue (SAR) operations, and creates a common situation awareness picture of the Naval Theatre. The system structure diagram is designed to solve computational overload problem when processing large volume of data received from radar stations. The measurement-level fusion algorithm is developed based on the JPDA framework, in which radar data received from a single or group of radars and AIS data is aggregated in a processing center. The servers and workstations make use of local area network (LAN), using standard Gigabit Ethernet technologies for local network communications. Acquisition, analysis, storage and distribution of target data is executed in servers, then the data is sent to automated operator stations (console), where functional operations for managing, identifying and displaying of target on digital situational map are performed.